The Role of the Oral Immune System in Oropharyngeal Candidiasis-Facilitated Invasion and Dissemination of Staphylococcus aureus - Pasman, Raymond; Krom, Bastiaan P.; Zaat, Sebastian A. J.; Brul, Stanley (Frontiers in Oral Health, 2022)
Candida albicans and Staphylococcus aureus account for most invasive fungal and bacterial bloodstream infections (BSIs), respectively. However, the initial point of invasion responsible for S. aureus BSIs is often unclear. Recently, C. albicans has been proposed to mediate S. aureus invasion of immunocompromised hosts during co-colonization of oral mucosal surfaces. The status of the oral immune system crucially contributes to this process in two distinct ways: firstly, by allowing invasive C. albicans growth during dysfunction of extra-epithelial immunity, and secondly following invasion by some remaining function of intra-epithelial immunity. Immunocompromised individuals at risk of developing invasive oral C. albicans infections could, therefore, also be at risk of contracting concordant S. aureus BSIs. Considering the crucial contribution of both oral immune function and dysfunction, the aim of this review is to provide an overview of relevant aspects of intra and extra-epithelial oral immunity and discuss predominant immune deficiencies expected to facilitate C. albicans induced S. aureus BSIs.